CTA's contribution on open data - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2015)
CTA is a member of the Global Open Data for Agriculture and Nutrition initiative which recently met in Wageningen to discuss the actual and potential impacts of Open Data on development. Here are nine things we learnt from the GODAN meeting.